Learning from museums : visitor experiences and the making of meaning - Falk, John H. (John Howard), 1948-; Dierking, Lynn D. (Lynn Diane), 1956- (Walnut Creek, CA : AltaMira Press, 2000)
Learning from Museums: An Introduction -- The Personal Context -- The Sociocultural Context -- The Physical Context -- Museums and the Individual -- Communities of Learners -- A Place for Learning -- The Contextual Model of Learning -- Documenting Learning from Museums -- Making Museums Better Learning Experiences -- Museums in the Larger Society -- The Future of Museums
CCS Gent
Includes bibliographical references (p. 237-263) and index.
boek
Keywords: Museums -- Educational aspects; Museum visitors; Museum exhibits; Experiential learning; Active learning; Non-formal education